Lichtenstein’s Open Mesh Hernioplasty versus Desarda’s no Mesh Hernia Repair in Inguinal Hernia: A Prospective Interventional Study - Manasa Das; Sushanta Kumar Das; Sunil Kumar Pattnaik; Shreya Jain; V Karthikarajam; Chirumamilla Naga Harsha Vardhan (Journal of Clinical and Diagnostic Research, 2025)
Introduction: Inguinal hernia repair with mesh is a common surgical procedure in the abdomen, involving the implantation of a mesh at the weak point of the abdominal wall. However, due to postoperative complications and a slower recovery rate, alternative methods, like Desarda’s tissue repair method, have been introduced. Aim: To compare the short-term outcomes of Desarda’s no-mesh technique and Lichtenstein’s mesh repair in inguinal hernia patients, focusing on postoperative pain, incidence of complications and recurrence. Materials and Methods: A prospective interventional study was conducted in the Department of General Surgery at the Kalinga Institute of Medical Sciences, Bhubaneswar, Odisha, India, from June 2022 to May 2024. The authors enrolled 108 patients with primary uncomplicated inguinal hernias aged over 18 years, of which 54 patients underwent Desarda’s repair (Group 1) and 54 patients underwent Lichtenstein’s mesh hernioplasty (Group 2). Clinico-demographic features, Visual Analogue Scale (VAS) scores for postoperative pain and postoperative complications were compared between both groups. Statistical significance was assessed using the Chi-square test or Student’s t-test. Results: Each group comprised 54 patients, with mean ages of 47.5±16.3 years for Group 1 and 44.2±14.9 years for Group 2. A significant difference (p=0.006) in the incidence of seroma was observed between the two groups. When comparing both groups, Group 1 patients reported significantly less pain on Postoperative Day (POD) 1 (p=0.03). The recovery rate was faster in the Desarda group (7.61±1.21 days) compared to the Lichtenstein group (8.28±1.29 days). Conclusion: The Desarda technique was found to be a more effective method, offering a shorter duration of surgery and faster recovery. Thus, Desarda’s procedure should be considered as an alternative to mesh-based treatments.